Evaluasi Efektivitas Implementasi Marketing Mix (Bauran Pemasaran) pada UMKM di Sektor Jasa Laundry - Qanita Najla; Revaldi Hermawan Bugis; Riza Mukhtia; Zainarti Zainarti (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to evaluate the effectiveness of the implementation of the marketing mix in SMEs in the laundry service sector, focusing on the 7P elements: product, price, promotion, place, process, people, and physical evidence. The research uses a descriptive qualitative method with data collection techniques including interviews, observations, and documentation with laundry business owners. The results show that a diverse range of services, competitive pricing, strategic location, and structured work processes contribute to the sustainability of the business. However, challenges such as unpredictable weather, timeliness, limited facilities, and suboptimal promotion still pose barriers to improving service quality. The findings highlight the importance of strengthening digital promotion, modernizing equipment, and improving the accuracy and consistency of human resources (HR) to enhance the effectiveness of the marketing mix. With improvements in these areas, laundry SMEs can enhance their competitiveness and provide better service to customers, thus strengthening their position in a competitive market.